NEWS PRESENTATION STYLE ON SOCIAL MEDIA TIKTOK (CASE STUDY OF SCTV COVERAGE 6 PROGRAM) - Muhtadin, Muhammad Habil; Fransiskus Xaverius Yatno Karyadi; Wahyu Nova Riski (Kirana Publisher, 2024)
This study aims to analyze the presentation style of television news on TikTok social media, with a focus on SCTV's Liputan 6 news program. Social media platforms such as TikTok have become an important channel for news distribution, which requires a different approach from traditional news presentation on television. This research uses a qualitative method with a case study approach to understand how Liputan 6 SCTV presents news on TikTok, as well as to identify the elements that make presenting news on this platform effective and attractive to audiences. Data collection techniques through observation interviews, and documentation. The results showed that the adaptation of the presentation of news on television to TikTok by Liputan 6 SCTV adopts a more concise format and duration, uses interesting visuals, with a light narrative, can interact with the audience compared to the presentation of news on television. Classifying news content that most often gets attention by the audience so that it becomes viral, this classification is based on the type of news uploaded. And Liputan 6 utilizes Agenda Setting Theory in each of their TikTok content by highlighting news that has a significant impact on the public